A rare case of pediatric volvulus caused by a persistent omphalomesenteric cyst - Valpaços,Catarina (2018)
A persistent omphalomesenteric duct is one possible cause of small-bowel volvulus, a rare cause of acute abdomen in children. A four-year-old child was admitted to the Emergency Department with abdominal pain and incoercible vomiting, with neither abdominal guarding nor relevant abnormalities revealed in complementary diagnostic exams. Due to a significant clinical deterioration over a 48-hour observation period, the child was transferred to a tertiary hospital with pediatric surgery. An abdominal ultrasound revealing severe bowel distension and increased abdominal free fluid warranted an exploratory surgery, which identified a voluminous omphalomesenteric duct cyst. When symptomatic, treatment of this condition is consensual and consists of surgical excision of the anatomical abnormality, either by laparoscopy or conventional surgery. The latter was performed. Conclusion: A persistent omphalomesenteric duct is a rare condition that generally requires a high level of clinical suspicion for diagnosis to be made, being most commonly detected during surgery. Associated complications and mortality rates are high, and a timely intervention is key, since surgical removal is the only treatment option.